Soil genesis and landscape evolution along a toposequense of Rio Araguari, Central Brazil - Neufeldt, Henry; Griesinger, Marilena Oliveira; Zech, Wolfgang (Sociedade & Natureza, 2000)
Soil genesis and landscape evolution along a toposequense of Rio Araguari, Central Brazil..........